Biodiversity in Areas Beyond National Jurisdiction (BBNJ): the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) and the United Nations BBNJ agreement. Issue 2 (3rd July 2021) - Haward, Marcus
ABSTRACT: The Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) has addressed the management of biodiversity in areas beyond national jurisdiction since its establishment under the 1980 Convention on the Conservation of Antarctic Marine Living Resources (CAMLR Convention). The development of a draft Agreement under the United Nations Convention on the Law of the Sea on the Conservation and Sustainable Use of Marine Biological Diversity of Areas Beyond National Jurisdiction (BBNJ Agreement) reinforces the significance of conservation oriented, ecosystem-based management in areas beyond national jurisdiction pioneered by CCAMLR. This paper explores the potential interplay between CCAMLR and the BBNJ Agreement, noting that while the BBNJ Agreement commits not to 'undermine relevant legal instruments and frameworks and relevant global, regional, subregional and sectoral bodies', it is likely to sharpen assessments of CCAMLR's performance.